A new schedule of fotemustine in temozolomide-pretreated patients with relapsing glioblastoma - Addeo, Raffaele (Springer US, 2010)
In the present study we investigated the feasibility and effectiveness of a new biweekly schedule of fotemustine (FTM) in patients with recurrent glioblastoma, after at least one previous treatment. The primary endpoint was progression-free survival at 6 months; secondary objectives were clinical response, overall survival, disease-free survival, and toxicity. Forty patients (median age 52.8 years; median Karnofsky Performance Status at progression 90) underwent second-line chemotherapy with FTM. Selected patients were previously treated with a standard radiotherapy course with concomitant temozolomide (TMZ). After tumor relapse or progression proven by magnetic resonance imaging (MRI), all patients underwent chemotherapy with FTM, given intravenously at dose of 80 mg/m(2) every 2 weeks for five consecutive administrations (induction phase), and then every 3 weeks at 100 mg/m(2) as maintenance. A total of 329 infusions were administered; the median number of cycles administered was 8. All patients completed the induction phase, and 29 patients received at least one maintenance infusion. Response to treatment was assessed using MacDonald criteria. One complete response [2.5%, 95% confidence interval (CI): 0–10%], 9 partial responses (22.5%, 95% CI: 15–37%), and 16 stable diseases (40%, 95% CI: 32–51%) were observed. Median time to progression was 6.7 months (95% CI: 3.9–9.1 months). Progression-free survival at 6 months was 61%. Median survival from beginning of FTM chemotherapy was 11.1 months. The schedule was generally well tolerated; the main toxicities were hematologic (grade 3 thrombocytopenia in two cases). To the best of our knowledge, this is the first report specifically dealing with the use of a biweekly induction schedule of FTM. The study demonstrates that FTM has therapeutic efficacy as single-drug second-line chemotherapy with a favorable safety profile.